Increasing The Role Of Rail-Based Public Transportation Through Improving Services And Developing T.O.D Area To Reduce Congress In Jakarta - Soemino Eko Saputro; Edi Abdurachman; Prasadja Ricardianto; Julison Arifin (Dinasti Publisher, 2024)
Abstract: The problems that cause public transportation are less desirable because the railway network is still very limited, public transportation services still need to be improved, full integration has not been realized and the development of Transit Oriented Development cannot be implemented. The purpose of this study was to determine whether the service model and public policy were successful, therefore the study used variables, namely; Perceived Quality; Trust; Passenger Satisfaction; Perceived Value; Passenger Preference; Passenger Loyalty, Behavior Intention to Purchase, and Transit Oriented Development as moderation and Passenger preference as intervening variables. Data analysis methods in this study include Importance and Performance Analysis (IPA), and Structural Equation Model (SEM) with the help of the SMART PLS 4 program and this study used a sample of 400 respondents, namely train users. Based on the results of the analysis Perceived quality, Passenger satisfaction, Trust, Passenger preference, and Passenger loyalty can have a positive and significant influence on behavior intention to purchase but Perceived value does not have a significant influence on the development of transit-oriented development can have a significant influence on loyalty and behavior intention to purchase. In Important performance analysis to improve service performance, namely unhindered train travel, high reliability, integrated and single ticket system.